The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1155/2022/7195699
|View full text |Cite
|
Sign up to set email alerts
|

Influence of High-Frequency Repetitive Transcranial Magnetic Stimulation on Neurobehavioral and Electrophysiology in Patients with Disorders of Consciousness

Abstract: Objective. High-frequency repetitive transcranial magnetic stimulation (HF-rTMS) has been proposed as a promising therapeutic intervention for patients with disorders of consciousness (DOC). However, its therapeutic effects in the literature are inconsistently documented. The primary aim of this study was to explore the alterations in neural connectivity and neurobehavioral reactivity during rTMS modulation in patients with DOC. In addition, safety was investigated as a secondary aim. Methods. The presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
(98 reference statements)
0
7
0
Order By: Relevance
“…Results from assessment of bias using revised Cochrane risk-of-bias tool for parallel and cross-over studies were presented in Figures 2 , 3 . Only three studies were assessed as “low risks” (Peri et al, 2001 ; Chen et al, 2022 ; Fan et al, 2022 ). In addition, the majority of included studies ( n = 7) were assessed as “some concerns” because of indistinct illustration of randomization process or other relatively rare reasons (Cooper et al, 1999 ; Huang et al, 2017 ; Thibaut et al, 2017 ; Zhang et al, 2017 ; He et al, 2018 ; Martens et al, 2018 ; Wu et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Results from assessment of bias using revised Cochrane risk-of-bias tool for parallel and cross-over studies were presented in Figures 2 , 3 . Only three studies were assessed as “low risks” (Peri et al, 2001 ; Chen et al, 2022 ; Fan et al, 2022 ). In addition, the majority of included studies ( n = 7) were assessed as “some concerns” because of indistinct illustration of randomization process or other relatively rare reasons (Cooper et al, 1999 ; Huang et al, 2017 ; Thibaut et al, 2017 ; Zhang et al, 2017 ; He et al, 2018 ; Martens et al, 2018 ; Wu et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our recent study, it was found that using high-frequency rTMS to stimulate the injured part of the patient's affected side has a positive effect on the recovery of consciousness after TBI (Shen et al, 2019). In patients with effective treatment, it was found that the "motor" score in the CRS-R scale improved significantly, and the patient's prognosis was also better.…”
Section: Introductionmentioning
confidence: 93%
“…Similar to the choice of target in the protocol of tDCS, bilateral DLPFC and left M1 were also the most common targets in the TMS protocol. Six papers [39][40][41]44,45,49 reported its use in DLPFC, one session in left DLPFC 41 showed positive results only in the MCS group, and the other five (four in left DLPFC, 40,44,45,49 one in right DLPFC 39 ) all showed positive results in the real rTMS group. Two randomized sham-control trials selected M1 as the target.…”
Section: Choice Of Targetmentioning
confidence: 99%
“…Most of the past studies have used the CRS‐R scale as well as electrophysiological methods such as EEG, TMS‐EEG, brainstem auditory‐evoked potential (BAEP), and somatosensory‐evoked potential (SEP) to assess the effectiveness and changes in brain activity evoked by TMS 39,41,44,45,47,49 . In the last 5 years, electrophysiological methods have remained the primary means of assessment.…”
Section: Innovations In Transcranial Magnetic Stimulationmentioning
confidence: 99%
See 1 more Smart Citation